Implementation of Collision Avoidance System Algorithm in NPC Game 3D - Gugah Alwan Hamanako; Adi Sucipto (Journal of Information Technology and Its Utilization, 2023)
Nowadays, with the rapid development of technology, we are given the convenience of finding entertainment such as games. Now this game can be quickly run on various media, one of them is a smartphone. Most smartphones' operating systems (OS) are Android and IOS. Among the both of OS which is currently popular is Android. This research aims to create an Artificial Intelligent of Non-Player Character (NPC) that can avoid every obstacle using the Collision Avoidance System algorithm. The result of the research is an android game app that applies the Collision Avoidance System that can make AI NPC avoid obstacles. The application of the algorithm to the NPC is made in 3 stages, namely, design by making a flowchart of the algorithm, then writing a program from the Collision Avoidance System, and finally, testing the AI ​​NPC. The test is carried out by comparing the reactions of NPC 1 and NPC 2 in passing through obstacles when on different paths by being carried out jointly between NPC. Based on the tests on AI NPC, NPC managed to avoid obstacles in front of them and the players, and it is almost 93% successful.